2019
DOI: 10.1111/dom.13605
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effect of saxagliptin and glimepiride with a composite endpoint of adequate glycaemic control without hypoglycaemia and without weight gain in patients uncontrolled with metformin therapy: Results from the SPECIFY study, a 48‐week, multi‐centre, randomized, controlled trial

Abstract: Aims: To compare the efficacy and safety of saxagliptin and glimepiride in type 2 diabetes (T2D) patients who are inadequately controlled with metformin monotherapy. Materials and methods:In this 48-week, multi-centre, open-label, randomized, parallel trial (NCT02280486, clinicaltrials.gov), a total of 388 T2D patients were randomized 1:1 to saxagliptin or glimepiride groups. The primary endpoint was achievement of HbA1c <7.0%, without hypoglycaemia, defined as blood glucose <3.9 mmol/L and weight gain <3.0% a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 33 publications
(49 reference statements)
2
3
0
Order By: Relevance
“…A meta‐regression analysis of 78 randomized controlled trials with 20,053 patients showed that DPP‐4 inhibitors have greater efficacy in reducing HbA1c in patients with higher baseline values, with a 0.26% incremental reduction in the HbA1c response for every 1% increase of baseline HbA1c ( P < 0.001) 13 . Similar results were reported in the SUNSHINE and SPECIFY trials in Chinese patients with type 2 diabetes 9,12 . In the SUNSHINE trial, saxagliptin treatment was associated with larger reductions in HbA1c in patients with higher baseline values – the reductions in HbA1c ranged from –0.78% in patients with baseline HbA1c of <8.0% to –2.90% in those with baseline HbA1c ≥10.0% to ≤11% 9 .…”
Section: Discussionsupporting
confidence: 73%
See 2 more Smart Citations
“…A meta‐regression analysis of 78 randomized controlled trials with 20,053 patients showed that DPP‐4 inhibitors have greater efficacy in reducing HbA1c in patients with higher baseline values, with a 0.26% incremental reduction in the HbA1c response for every 1% increase of baseline HbA1c ( P < 0.001) 13 . Similar results were reported in the SUNSHINE and SPECIFY trials in Chinese patients with type 2 diabetes 9,12 . In the SUNSHINE trial, saxagliptin treatment was associated with larger reductions in HbA1c in patients with higher baseline values – the reductions in HbA1c ranged from –0.78% in patients with baseline HbA1c of <8.0% to –2.90% in those with baseline HbA1c ≥10.0% to ≤11% 9 .…”
Section: Discussionsupporting
confidence: 73%
“…The efficacy and safety of saxagliptin as monotherapy or combination therapy in Chinese patients with type 2 diabetes have been established in several studies 9‐12 . In the present study, saxagliptin as add‐on to metformin has shown consistent glycemic efficacy across a range of patient profiles.…”
Section: Discussionsupporting
confidence: 54%
See 1 more Smart Citation
“…We included 82 randomised controlled trials (fig 1) with 104 833 participants with type 2 diabetes in the traditional pairwise meta-analysis 343536373839404142434445464748495051525354555657585960616263646566676869707172737475767778798081828384858687888990919293949596979899100101102103104105106107108109110111112113114115. Characteristics of studies and participants included in the pairwise meta-analysis are shown in table 1 and supplementary table C. The average age of participants was 59.4 years, and 39.7% (n=41 618) were female.…”
Section: Resultsmentioning
confidence: 99%
“…Glimepiride is a long-acting sulfonylurea compound and, like other sulfonylureas, it can cause episodes of hypoglycemia and increase the body weight [1]. It has a beneficial effect on insulin resistance by producing better glycemic control [2]. Several studies highlight a non-harmful effect of glimepiride against cardiac diseases, but it carried also a higher risk of stroke [3].…”
Section: Introductionmentioning
confidence: 99%